FANCM c.5101C>T mutation associates with breast cancer survival and treatment outcome. Issue 12 (19th September 2016) - Kiiski, Johanna I.; Fagerholm, Rainer; Tervasmäki, Anna; Pelttari, Liisa M.; Khan, Sofia; Jamshidi, Maral; Mantere, Tuomo; Pylkäs, Katri; Bartek, Jiri; Bartkova, Jirina; Mannermaa, Arto; Tengström, Maria; et al.
Abstract : Breast cancer (BC) is a heterogeneous disease, and different tumor characteristics and genetic variation may affect the clinical outcome. The FANCM c.5101C > T nonsense mutation in the Finnish population associates with increased risk of breast cancer, especially for triple‐negative breast cancer patients. To investigate the association of the mutation with disease prognosis, we studied tumor phenotype, treatment outcome, and patient survival in 3, 933 invasive breast cancer patients, including 101 FANCM c.5101C > T mutation carriers and 3, 832 non‐carriers. We also examined association of the mutation with nuclear immunohistochemical staining of DNA repair markers in 1, 240 breast tumors. The FANCM c.5101C > T mutation associated with poor 10‐year breast cancer‐specific survival (hazard ratio (HR)=1.66, 95% confidence interval (CI) 1.09–2.52, p  = 0.018), with a more pronounced survival effect among familial cases (HR = 2.93, 95% CI 1.5–5.76, p  = 1.80 × 10 −3 ). Poor disease outcome of the carriers was also found among the estrogen receptor (ER) positive subgroup of patients (HR = 1.8, 95% CI 1.09–2.98, p  = 0.021). Reduced survival was seen especially among patients who had not received radiotherapy (HR = 3.43, 95% CI 1.6–7.34, p  = 1.50 × 10 −3 ) but not among radiotherapy treated patients (HR = 1.35, 95% CI 0.82–2.23, p  = 0.237). Significant interaction was found between the mutation and radiotherapy ( p  = 0.040). Immunohistochemical analyses show that c.5101C > T carriers have reduced PAR‐activity. Our results suggest that FANCM c.5101C > T nonsense mutation carriers have a reduced breast cancer survival but postoperative radiotherapy may diminish this survival disadvantage. Abstract : What's new? Variations in DNA repair genes can predispose individuals to breast cancer, with one example being FANCM c.5101C > T, a nonsense mutation in the Fanconi Anemia DNA repair pathway. In previous work, FANCM c.5101C > T was associated with increased breast cancer risk in the Finnish population. Here, the mutation is further shown to be associated with adverse breast cancer outcome. Mutation‐positive Finnish patients exhibited reduced long‐term survival and increased risk of disease recurrence. Survival was worse particularly for patients who were not treated with radiotherapy, indicating that FANCM c.5101C>T may interact with radiotherapy to improve disease outcome in mutation carriers.